SHOX Duplication and Tall Stature in a Patient with Xq Deletion and Vascular Disease. (8th April 2019) - Ramirez, J. M.; Rodríguez, F. A.; Echeverría, M. I.; Vargas, A. L.; Calderón, A. E.; Miatello, R. M.; Renna, N. F.
Abstract : The anomalies of X chromosome are classified as numerical or structural. Concomitant structural anomalies in this chromosome that associate partial loss of its long arm with duplications in its short arm are uncommon. Only a few cases have been published and in most of them the reported patients present ovarian dysfunction, tall stature, and overdosage of the SHOX gene with locus Xp22.33. Considering these reports, we evaluated the case of a woman with a deletion in the long arm of the X chromosome, premature ovarian failure, tall stature, and multiple arterial vascular disease. With the aim to find a relationship between karyotype and phenotype, we explored associated anomalies in Xp and certified the overdosage of the SHOX gene in this case by MLPA. Also, taking into account the fact that the gene locus of the angiotensin-converting enzyme type 2 (ACE2) is located in Xp, our goal was to investigate the influence of this gene in the development of cardiovascular disease. The detection of the gene product of ACE2 by ELISA was undetectable. We have proposed that cytogenetic anomalies in X chromosome could contribute to decrease this protein synthesis in this gender.